Saussure’s Law, the nom. pl. in ‑ai, and the treatment of acute diphthongs in final syllables in Lithuanian - Jasanoff, Jay H. (Baltistica, 2016)
This paper addresses the relationship of the Lith. nom. pl. endings ‑ai (‑aĩ) and ‑i, ‑ie (‑ì, ‑ìe) to each other and to their common source, the PIE pronominal nom. pl. in *‑oi. It is argued that the Proto-BSl. preform was *‑ai, with acuteness analogically taken from the corresponding nominal ending *‑ōs. Proto-BSl. *‑ai, which developed regularly to ‑i in Slavic and to ‑ai in Old Prussian, had two reflexes in Lithuanian. The phonologically regular treatment is seen in the pronominal and adjectival ending ‑i(e), which developed from *‑ai to *‑ẹ̄ via the presumed intermediate stage *‑ɛi. The nominal ending ‑ai is a morphological treatment of the same sequence, with a) *‑ɛi remade to *‑ai under the influence of paradigmatically related forms in *‑a‑, and b) acuteness subsequently lost in a final syllable. The second step runs counter to standard opinion, which holds that underlying acute diphthongs in final syllables trigger Saussure’s Law and retain their acuteness in Žemaitian, as in the ā‑present forms 1 sg. sakaũ, 2 sg. sakaĩ (Žem. sakâu, sakā̂). It is maintained here, however, that the verbal endings that appear as ‑aũ and ‑aĩ in standard Lithuanian are not historically diphthongs at all, but contracted sequences that arose after the “de-acuting” of the inherited nom. pl. in *‑ai to ‑ai and before Saussure’s Law. A byproduct of this explanation is that other descriptively non-acute diphthongs in final syllables, notably the dat. sg. in ‑ui (< PIE *‑ōi) and the instr. pl. in ‑ais (< PIE *‑ōis), can also be assumed to have been originally acute, as their etymologies require.